PENGGUNAAN APLIKASI E-RAPOR KURIKULUM MERDEKA KELAS X DI SMK NEGERI 1 PULAU PUNJUNG DHARMASRAYA - Via Dwi Putri; Liza Husnita; Ranti Nazmi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study aims to describe the use of the independent curriculum e-report card application for class X at SMK Negeri 1 Pulau Punjung Dharmasraya. After that, it describes the assessment of the use of the e-Report card application at SMK Negeri 1 Pulau Punjung Dharmasraya. This was motivated by changes in the processing of student values which were initially done manually and then changed to a value processing application in the form of e-Reports. The transition from manual grade processing to the e-Report card application, especially at SMK Negeri 1 Pulau Punjung Dharmasraya which was selected as one of the schools that uses the e-Report card application for value processing. Changes in processing from manual to e-Reports can be seen from four aspects, namely teacher understanding, planning, process, and assessment of the use of the independent curriculum e-Reports application for class X at SMK Negeri 1 Pulau Punjung Dharmasraya. This research method is descriptive qualitative with data collection techniques of observation, interviews, and documentation. The results of this study indicate that the e-Raport application provides many conveniences for educators to process student grades.Â The implementation of the Class X Independent Curriculum e-Raport Application at SMK Negeri 1 Pulau Punjung Dharmasraya was attended by all teachers teaching in Class X, consisting of subject teachers, homeroom teachers, and vocational subject teachers. At the stage of the teacher's value input process, the steps are in accordance with the e-Raport guidelines. Assessment of the use of the e-Raport Application is intended to minimise difficulties; if not evaluated, it will complicate performance. So the main goal is to find out what the obstacles are to inputting values using e-Reports. Basically, the e-Raport is here to help teacher performance in the assessment aspect and make it more efficient. So because e-Reports have provided many conveniences, there are not many problems.